'Learning how to go on': refugee students and informal learning practices. Issue 11 (18th September 2020) - Kaukko, Mervi; Wilkinson, Jane
ABSTRACT: This article explores the social and historical formation of 'successful' refugee students' learning practices utilising in-depth, critical incident interviews with primary school aged, refugee-background students in Australia. Employing a practice lens, this article firstly explores the informal learning practices the students identify from their past; secondly, examines the arrangements which hold these learning practices in place, and thirdly, explicates the ways in which these practices may enable students' educational achievement in their current host country. We conclude that despite difficult starting points and educational gaps, many refugee students find ways to learn and succeed in school, but such achievement should not be a matter of serendipity. Inclusive schools must acknowledge not only the challenges in refugee students' learning, but also the resources they bring into their education.